Spectral analysis of type II supernovae. Issue Volume 9:Issue S296(2013) (29th January 2014) - Gutiérrez, Claudia P.; Anderson, Joseph; Hamuy, Mario; Folatelli, Gastón; ,
Abstract: We present spectroscopic analysis of 63 type II supernovae. We present preliminary results on correlations between spectroscopic and photometric properties, focusing on light-curve decline rates, absolute magnitudes and H α lines profiles. We found the ratio of absorption to emission of H α P-Cygni profile as the dominant measured parameter as it has the highest median correlation with all other parameters.